Orthodeoxia without Platypnea in Hereditary Hemorrhagic Telangiectasia in the Presence of a Cerebral Abscess and Multiple Pulmonary Arteriovenous Malformations: Unusual Complications and Transcatheter Endovascular Treatment - Carlos Salazar; Jacky Bruce Blank; Veronica Palmero (Case Reports in Pulmonology)
Hereditary hemorrhagic telangiectasia is a rare autosomal-dominant condition affecting visceral blood vessel development. Cerebral and most commonly pulmonary arteriovenous malformations are found in the majority of symptomatic patients. The most common complications include embolic strokes and cerebral abscesses, which have been attributed to abnormal vessel communications. Platypnea orthodeoxia is a rare condition that presents dyspnea and oxygen desaturation when adopting an upright position and is relieved on decubitus. The association between hereditary hemorrhagic telangiectasia, pulmonary arteriovenous malformations, and platypnea orthodeoxia has been described in medical literature; however, orthodeoxia as a single entity without platypnea has not been described yet, especially associated with complications of this hereditary condition. We present the case of a 38-year-old male with persistent headaches, in whom a cerebral lesion was detected. Orthostatic tachycardia and severe orthodeoxia without platypnea were evidenced during physical examination. The patient was subsequently diagnosed with hereditary hemorrhagic telangiectasia and underwent cerebral abscess drainage as well as transcatheter endovascular closure of multiple pulmonary arteriovenous malformations. For this reason, the concept of platypnea orthodeoxia syndrome needs further revision. Patients presenting refractory hypoxemia should warn physicians to initially evaluate their oxygen saturation measurements during standing and decubitus position, even though platypnea may not be present.